Analisis Kesehatan di Sekolah Dasar Negeri Dukuh Kupang - Ilham Nur Reza Sigit; Muhammad Arfidan Syafatullah; Amanda Febtyandi; M. Randy; Arijalur R; Salsa Sabilillah; Moch Felly Assahl; Riki Dyan Sahputra (Nusa Cendana University, 2025)
Objective: This study aims to analyze the health status of students at SD Negeri Dukuh Kupang I-488, including their nutritional status and the health of their eyes, ears, nose, teeth and mouth, neck, and extremities. Methods: This study employed a quantitative descriptive method with an observational approach. The study subjects were all students present at the time of the examination (112 students). The examination included anthropometric measurements (height and weight), eye examinations (visual acuity, color blindness, conjunctiva, sclera), ears (earwax), nose (signs of upper respiratory tract infection), neck (thyroid), teeth and mouth (caries, hygiene), and extremities (tremor). Data were analyzed descriptively in terms of frequency and percentage. Results: The results showed that 31.2% of students had abnormal nutritional status (16.1% underweight, 19.6% overweight). Reduced visual acuity was found in 12.5% of students, earwax in 13.4%, dental caries in 27.7%, poor oral hygiene in 25%, signs of upper respiratory tract infection (URTI) in 9.8%, pale conjunctiva in 8%, partial color blindness in 2.7%, and tremors in 0.9%. No thyroid enlargement was found. Conclusion: Health issues such as abnormal nutritional status, decreased visual acuity, dental caries, and earwax buildup were found at relatively high rates. Monitoring and follow-up by the school, parents, and medical personnel are necessary to support the students’ health on an ongoing basis.